Paratubal Cystectomy in a Pregnant Woman Using the Single-Incision Laparoscopic Surgery (SILS) Technique - Luke William Nelson; Elliot MacKenzie (Hindawi Limited, 2022)
Introduction. The proliferation of prenatal ultrasound has enhanced the detection of adnexal masses during pregnancy. The presentation necessitates a clear approach to investigation and treatment that balances both maternal and fetal risk. Laparoscopy is a safe approach to surgical management in the pregnant patient, and SILS may contribute to minimising perioperative complications. Case Presentation. We present the case of a 21-year-old female in her second trimester of pregnancy presenting with a large 20 cm right adnexal cyst. We proceeded with laparoscopic cystectomy via the SILS technique. There were no intraoperative complications, and she recovered well postoperatively. Conclusion. Laparoscopic resection of adnexal lesions is safe during pregnancy and should be favoured over the open approach. SILS minimises incision sites and has potential for reduction in perioperative morbidity.